The Time Budget of Javan Deer (Rusa timorensis, Blainville 1822) in Panaitan Island, Ujung Kulon National Park, Banten, Indonesia - . Pairah; YANTO SANTOSA; LILIK BUDI PRASETYO; ABDUL HARIS MUSTARI (HAYATI Journal of Biosciences, 2014)
Javan deer that exist in Panaitan Island was reintroduced from Peucang Island during 1978-1982. We observed behavior of the reintroduced Javan deer inhabiting Panaitan Island. Javan deer in this island spent most of their diurnal time for feeding. There were no significant differences between all age-sex variation for all activities pattern. The behavior of Javan deer was influenced by age, sex, social group, temperature, and food availability.